Epidural administration of anesthetics and corticosteroids in treatment of acute radicular pain syndrome of lumbar spine in neurosurgical department - Olkhov, Valeriy; Buyanov, O.; Horbatyuk, Kostyantyn; Kudina, O.; Ventskivskiy, Leonid; Borodenko, O.; Kirichenko, Volodymyr; Ventskivskiy, Ivan; Chyrka, Iurii; Dolgopolova, Ruslana (Ukrainian Neurosurgical Journal, 2015)
The purpose. To estimate efficacy of epidural administration corticosteroids and local anesthetics at radicular pain syndromes associated with discoradicular conflict in lumbar spine. Materials and methods. Epidural injection of corticosteroids and local anesthetics were used in 348 patients with radicular pain syndromes in lumbar spine in the Neurosurgical Department of Vinnytsa Regional Psychoneurological Hospital. Procedures were performed in the operating room under local anesthesia. We administrated betamethasone 2 ml and bupivacaine 0.5% 5 ml. Results. Positive result was achieved in 86.8% cases. As a rule patients reported a reduction in pain intensity right after the procedure, the effect increased on the 2nd–3rd day. In 54 (15.5%) patients pain intensity reduced by 30–50% after the first injection, so we performed it again. In 46 (13.2%) patients there was no relief, they were operated for intensive pain. Conclusions. Epidural administration of corticosteroids and local anesthetics is an effective method of neurosurgical treatment of pain syndromes in the lumbar spine and radicular pain caused by inflammation, this method is characterized by low risk level and is used as a criteria for determining whether to perform surgery.